EGFR-targeted prodrug activation using bioorthogonal alkene-azide click-and-release chemistry. (15th September 2021) - Fairhall, Jessica M.; Camilli, Júlia C.; Gibson, Blake H.; Hook, Sarah; Gamble, Allan B.
Graphical abstract: Abstract: Epidermal growth factor receptor (EGFR) is overexpressed in many cancers and therefore serves as an excellent target for prodrug activation. Functionalised trans- cyclooctenes (TCO) were conjugated to an EGFR antibody (cetuximab), providing a reagent for pre-targeting and localisation of the bioorthogonal reagent. The TCOs react with a 4-azidobenzyl carbamate doxorubicin prodrug via a [3 + 2]-cycloaddition and subsequent self-immolation leads to release of doxorubicin (click-and-release). In vitro cell-based assays demonstrated proof-of-concept, that cetuximab conjugated to highly strained TCO (AB-d-TCO) could bind to the EGFR in a melanoma cell line, and selectively activate the doxorubicin prodrug. In a non-EGFR expressing melanoma cell line, no significant prodrug activation was observed. In vivo experiments using this combination of AB-d-TCO and the azido-doxorubicin prodrug in a murine melanoma model revealed no significant anti-tumour activity or increased survival, suggesting there was insufficient prodrug activation and drug release at the tumour site.